1977
DOI: 10.1002/1097-0142(197707)40:1+<509::aid-cncr2820400717>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of lethal action of arabinosyl cytosine (araC) and arabinosyl adenine (araA)

Abstract: Certain D-arabinosyl nucleosides, notably arabinosyl cytosine (araC) and arabinosyl adenine (araA), are useful in the treatment of certain leukemias and some DNA virus infections, respectively. The compounds are lethal to animal cells and some bacteria. Despite extensive deamination, the parent nucleosides are transported within sensitive cells and phosphorylated to the mono-, di-and triphosphates. AraCTP and araATP are good specific competitive inhibitors of tumor cell or virus-induced DNA polymerases, compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Ara-C is commonly used in the treatment of leukemias. Although Ara-C is active against a variety of DNA viruses (8), activity against an RNA virus has never been reported.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Ara-C is commonly used in the treatment of leukemias. Although Ara-C is active against a variety of DNA viruses (8), activity against an RNA virus has never been reported.…”
supporting
confidence: 83%
“…Ara-C is a powerful antimitotic drug (8). To test whether this affected BDV replication, we induced total growth arrest of Vero-BV cells using conventional mitotic inhibitors (5-fluoro-2Ј-deoxyuridine and uridine).…”
Section: Discussionmentioning
confidence: 99%
“…In view of our current study, this exonuclease activity could be much more important than that previously suggested. Besides L-OddC terminated oligonucleotide, we also examined the effectiveness of APE1 exonuclease activity against the antiviral deoxyoligonucleotides analogs L-SddC, L-Fd4C (33,34), ddC (35,36), L-ddC (37), and the anticancer analogs such as dFdC (38 -41) and araC (42,43) (Fig. 1).…”
mentioning
confidence: 99%
“…1), by phosphorylation to ara-CTP, and by deamination to ara-U (see Cohen, 1977, for a review). 1), by phosphorylation to ara-CTP, and by deamination to ara-U (see Cohen, 1977, for a review).…”
Section: Introductionmentioning
confidence: 99%